2015
DOI: 10.1021/jp5124184
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Temperature and Support on the Reduction of Cobalt Oxide: An in Situ X-ray Diffraction Study

Abstract: In situ X-ray diffraction was used to study the reduction of unsupported CoO, and Co3O4 under different conditions of time and temperature, and the effect of lanthanum, ruthenium, or zinc doping of γ-alumina on the reduction of supported cobalt oxide. The reduction of unsupported cobalt oxide (Co3O4) produced CoO, then hexagonal close-packed Co (Co(hcp)) and at temperatures above 400 °C, only face-centered cubic Co (Co(fcc)) was obtained. However, it was possible to obtain a mixture of Co(hcp) and Co(fcc) at 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(55 citation statements)
references
References 36 publications
1
54
0
Order By: Relevance
“…1 Table 3). The literature suggests that the cobalt on Co 1 La may be completely reduced to metallic form, which is active at the conditions tested here [40].…”
Section: The Function Of Copper In Higher Alcohol Synthesis Catalystsmentioning
confidence: 65%
“…1 Table 3). The literature suggests that the cobalt on Co 1 La may be completely reduced to metallic form, which is active at the conditions tested here [40].…”
Section: The Function Of Copper In Higher Alcohol Synthesis Catalystsmentioning
confidence: 65%
“…This result can be explained by the fact that the agglomeration of metallic iron atoms in the catalyst is much activated when reduction temperature is higher. [26][27][28][29]. All the peaks become narrow and sharpen with increasing reduction temperature.…”
Section: Characterization Of Fe-co/mgo Catalyst After Reductionmentioning
confidence: 93%
“…01-070-2855) and magnesium oxide (periclase, JCPDS card No. 01-071-1176) phases [26][27][28][29]. All the peaks become narrow and sharpen with increasing reduction temperature.…”
Section: Characterization Of Fe-co/mgo Catalyst After Reductionmentioning
confidence: 94%
See 1 more Smart Citation
“…In the case, some unstable catalysts are possibly reduced. For example, it is found that the reduction process of Co 3 O 4 under reducing gases is in this order: Co 3 O 4 →CoO→Co [23,24]. What is the influence of the catalyst valence state change for coal catalytic pyrolysis?…”
Section: Introductionmentioning
confidence: 99%